C-STEM Education: Chemistry-Centred Interdisciplinary Education - Liao, Qingling; Zhou, Qin; Mo, Zunli; Bao, Qianqian (Education Insights, 2026)
Regarded universally as the ’central science’, chemistry naturally serves as an indispensable interdisciplinary hub for the effective implementation of STEM (Science, Technology, Engineering, and Mathematics) education. Nevertheless, current STEM pedagogical practices within the field of chemistry are generally characterised by a concerning weakening of chemistry’s central role and a superficial approach to rigorous disciplinary thinking. Consequently, interdisciplinary integration often remains merely cosmetic, failing to leverage the true epistemological value of chemical sciences. To systematically address this critical gap, this paper proposes an innovative C-STEM educational philosophy that is firmly centred on chemistry. It constructs a comprehensive theoretical model for C-STEM education and meticulously clarifies the functional boundaries and complex mechanisms of interaction between chemistry and the other STEM disciplines. Furthermore, drawing upon the foundational pedagogical principles of authenticity, collaborative inquiry, project-based learning, and multidimensionality, this study designs a robust applied model for C-STEM. This framework details actionable implementation pathways for defining project objectives, structuring content, establishing real-world contexts, designing tasks, evaluating outcomes, and conducting holistic assessments. Extensive research and theoretical analysis indicate that the C-STEM approach, by steadfastly upholding the intrinsic value of chemistry while achieving deep, meaningful interdisciplinary integration, can provide a transformative theoretical framework and a highly practical paradigm. Ultimately, this model serves as a catalyst for the comprehensive reform of chemistry education and the effective localisation of STEM curricula in contemporary educational settings.